2021
DOI: 10.3390/environments8030019
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Year Monitoring of Ecosystem Metabolism in Two Branches of a Cold-Water Stream

Abstract: Climate change is likely to have large impacts on freshwater biodiversity and ecosystem function, especially in cold-water streams. Ecosystem metabolism is affected by water temperature and discharge, both of which are expected to be affected by climate change and, thus, require long-term monitoring to assess alterations in stream function. This study examined ecosystem metabolism in two branches of a trout stream in Minnesota, USA over 3 years. One branch was warmer, allowing the examination of elevated tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Our results show that ERwc increased (i.e., was faster) with increasing NO3-N, increasing DOC, and increasing temperature (Fig 6). Faster ERwc with increasing NO3-N, DOC, temperature in the Yakima River basin is unsurprising since nutrients, DOC, and temperature can drive 450 variation in stream metabolism (Honious et al, 2021;Hornbach, 2021;Bernot et al, 2010;Nakano et al, 2022). An increase with NO3-N may not always we expected, however, as Reisinger et al (2021) found that ERwc was faster with more NH4⁺ but slower with more NO3-N.…”
Section: Erwc Is Well-explained By Watershed Characteristics and Surf...mentioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that ERwc increased (i.e., was faster) with increasing NO3-N, increasing DOC, and increasing temperature (Fig 6). Faster ERwc with increasing NO3-N, DOC, temperature in the Yakima River basin is unsurprising since nutrients, DOC, and temperature can drive 450 variation in stream metabolism (Honious et al, 2021;Hornbach, 2021;Bernot et al, 2010;Nakano et al, 2022). An increase with NO3-N may not always we expected, however, as Reisinger et al (2021) found that ERwc was faster with more NH4⁺ but slower with more NO3-N.…”
Section: Erwc Is Well-explained By Watershed Characteristics and Surf...mentioning
confidence: 99%
“…Environmental features of rivers also influence their metabolism, including physical factors such as discharge (Bernhardt et al, 50 2022;Isabel et al, 2022;Hensley et al, 2019;Hotchkiss et al, 2015), flow regimes (Bernhardt et al, 2018;Ahmed and Abdul-Aziz, 2022;Clapcott and Barmuta, 2010), flow extremes (Hensley et al, 2019;Demars, 2019;Schiller et al, 2019), light availability (Bernhardt et al, 2022;Savoy and Harvey, 2021;Kirk et al, 2021;Cory et al, 2014;Savoy et al, 2021), and temperature (Hornbach, 2021;Jankowski and Schindler, 2019;Hotchkiss and Hall, 2014;Nakano et al, 2022); chemical factors including the availability of nutrients (Mulholland et al, 2008;Hoellein et al, 2007;Reisinger et al, 2021;Reisinger et al, 2015;55 Hall and Tank, 2003;Mulholland et al, 2001;Carlson and Poole, 2022) and the amount and quality of OM inputs and dissolved organic C (DOC) (Allan et al, 2021b;Garayburu-Caruso et al, 2020a;Bertuzzo et al, 2022;Zarnetske et al, 2011;Ellis et al, 2012); and watershed characteristics such as stream size or drainage area (Finlay, 2011;Hotchkiss et al, 2015), hydrologic connectivity (Hotchkiss et al, 2015;Rocher-Ros et al, 2019;Demars, 2019), watershed geomorphology (Jankowski and Schindler, 2019), and land use and land cover (Bernot et al, 2010;…”
Section: Introductionmentioning
confidence: 99%
“…Documenting and assessing the status of biological populations and communities and identifying sources of variation is a priority for ecological monitoring and management programs [1][2][3][4], including those in Canada's Oil Sands Region (OSR) [5]. Among the studies performed in the OSR to understand the effects of industrial developments, analyses of fish health indicators have been undertaken in streams in the minable sub-region since the late 1990s [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Diatomic diversity was instead used by Padula et al [4] to assess the ecological quality of small temporary high-elevation lakes in the Apennine mountains (Italy). Moreover, Hornbach [5] examined ecosystem metabolism over three years in two branches of a cold-water stream in Minnesota (USA), mainly differing in water temperature. Finally, two methodologies commonly used for the detection of hydrological alterations were coupled by Greco et al [6] in order to define the ecological flow of the Agri River (Italy).…”
mentioning
confidence: 99%
“…The results presented in this Special Issue should be taken into account for improving both the monitoring and management of freshwater resources: (i) the wide distribution of potential harmful bacteria from river runoff or direct sewage dumping has an impact on human health that should be urgently reduced [1], (ii) a critical requirement for the success of programs for the reintroduction of locally extinct species is the knowledge of the genetic diversity of the selected broodstocks to ensure self-sustainability of the reintroduced populations [2], (iii) taxon richness of benthic macroinvertebrates could be used as a surrogate indicator to assess the water quality when consolidate biomonitoring methods are not available [3], (iv) the presence of endangered diatomic species of particular conservational interest in temporary basins affected by extended drought periods triggers the need for conservation strategies for vulnerable and unstable environments strongly threatened by climate changes [4], (v) long-term monitoring of ecosystem metabolism is required to assess alterations in the function of streams affected by hydrological and temperature alterations exacerbated by the climate change [5], (vi) common operative tools should be implemented for ecological flow assessment in order to make water resource management more sustainable [6], (vii) organic farming and biocontrol could be an alternative to diffuse pollution by agrochemicals, while environmental flows and controlled sediment flushing operations could limit the hydropower impact on rivers [8]. Moreover, the review by Salmaso et al [7] could support the proper design of monitoring plans aimed at assessing the ecological impacts of hydropeaking and the effects of possible mitigation strategies.…”
mentioning
confidence: 99%